1996
DOI: 10.1172/jci118963
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-specific T cell tolerance to phospholipase A2 in bee venom immunotherapy and recovery by IL-2 and IL-15 in vitro.

Abstract: Bee venom phospholipase A 2 (PLA) is the major allergen in bee sting allergy. It displays three peptide and a glycopeptide T cell epitopes, which are recognized by both allergic and non-allergic bee venom sensitized subjects. In this study PLA-and PLA epitope-specific T cell and cytokine responses in PBMC of bee sting allergic patients were investigated before and after 2 mo of rush immunotherapy with whole bee venom. After successful immunotherapy, PLA and T cell epitope peptide-specific T cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
331
0
5

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(341 citation statements)
references
References 63 publications
5
331
0
5
Order By: Relevance
“…Clinical studies suggested that immunotherapy exerted its beneficial effect by anergy induction of allergen-specific Th2 cells, or by modulation of the Th2 response toward a Th1 or a regulatory T cell response (11)(12)(13). These observations resulted in various hypotheses on the mechanism of allergen immunotherapy encompassing roles for the dose of Ag (including t 1/2 and number of ligands expressed on the APC), the affinity of the TCR for the MHC-peptide complex, the type of APC (differences in costimulatory molecules and cytokines), and the route of administration (10, 14 -16).…”
Section: The Efficacy Of Immunotherapy In An Experimentalmentioning
confidence: 99%
“…Clinical studies suggested that immunotherapy exerted its beneficial effect by anergy induction of allergen-specific Th2 cells, or by modulation of the Th2 response toward a Th1 or a regulatory T cell response (11)(12)(13). These observations resulted in various hypotheses on the mechanism of allergen immunotherapy encompassing roles for the dose of Ag (including t 1/2 and number of ligands expressed on the APC), the affinity of the TCR for the MHC-peptide complex, the type of APC (differences in costimulatory molecules and cytokines), and the route of administration (10, 14 -16).…”
Section: The Efficacy Of Immunotherapy In An Experimentalmentioning
confidence: 99%
“…To investigate whether the Api m (1/2/3) is able to target specific T cells, the allergen-induced proliferative and cytokine responses in PBMC from BV-allergic 3 . In contrast to control animals, the Api m (1/2/ 3) and Api m 1 pretreatment resulted in the inhibition of Api m 1-specific IgE, IgG1 and IgG2a (Fig.…”
Section: Api M (1/2/3) Retains the Ability To Stimulate Human T Cellsmentioning
confidence: 99%
“…Two groups of female C57BL/6 mice (4-6 wk of age, n=6) were immunized s.c. with 100 lg/100 ll of Api m (1/2/3) and Api m 1 in saline 14, 10 and 6 days prior to i.p. immunization with 100 lg/100 ll of Api m 1/Al(OH) 3 . Control mice (n=6) received s.c. injections with saline alone.…”
Section: Induction and Regulation Of Specific Antibodies In Micementioning
confidence: 99%
See 2 more Smart Citations